Determinan Penghentian Penggunaan IUD di Indonesia - Nur Endah Permatasari; Dwi Martiana Wati; Andrei Ramani (Pustaka Kesehatan, 2013)
Contraceptive discontinuation is the big problem that can threat Family Planning (FP) program. Indonesia is one of the countries in the world that has increased the contraceptive discontinuation, especially IUD. The aim of this study was to analyze the determinants of IUD discontinuation in Indonesia. A cross sectional study design was used in this study. Data of this study were based on the results of IDHS 2007, with 706 samples. This research was analyzed using univariable analysis, bivariable analysis using Chi-square, and multivariable analysis using Logistic Regression with each significance level α=0,05. Residence, religion, economic status, exposure to mass media, FP information, and follow up of FP didn’t have significant relationship with IUD discontinuation. Age, parity, education, occupation, and FP discussion between husband-wife had significant relationship with IUD discontinuation. The factors that can be used to predict the IUD discontinuation were age, parity, and education. Keywords: IUD, Family Planning, Discontinuation